Psychological Practice Project Development “Women Victim Behavior in Domestic Violence Situations” - Artamonova V. V., Guremina N. V. (Psychology of Personal Interaction in Modern Society, 2024)
The study is devoted to psychological practice project development, analysis of psychological factors and characteristics of women victimized behavior in situations of domestic violence, aimed at studying the phenomenon of victimized behavior. An analysis of the basic phenomenon was carried out, a design toolkit for psychological practice was developed (a mind map of the concept, a sketch of the persona of a potential client), a schedule of thematic consultation meetings between the psychologist and the client was drawn up, and the organizational and managerial conditions for implementing the practice were determined.
Keywords: victim behavior; домашнее насилие; domestic violence; dysfunctional family; дисфункциональная семья; абьюз; виктимное поведение; женщины-жертвы; female victims; abuse